Patient cost analysis of a community-based teledermatology service versus conventional outpatient appointments in East Kent: a retrospective study through a societal lens to reduce health inequalities - Nurul Ain Nizar; Roopa Farooki; Piyush Mahapatra; Saul Halpern; Tim C. H. Hoogenboom (BMC Health Services Research)
Abstract Background The UK's National Health Service (NHS) is grappling with rising demand and limited dermatologists, leading to longer waiting times. This is particularly concerning for conditions like malignant melanoma, where early diagnosis is crucial. Teledermatology is being introduced to address these issues, but its impact on patients’ monetary and time costs, especially in deprived areas, is under-researched. This study investigates the impact of a community-based teledermatology model in East Kent, a coastal region with high cross-regional health inequalities. Methods We analysed the financial costs and time invested by patients undergoing community-based teledermatology versus if they were to attend traditional appointments. Data were gathered from 1368 referrals, from May 2022 to January 2024 at a secondary care provider in the region. We considered the diagnosis method, appointments, travel, monetary cost of time, parking costs and Index of Multiple Deprivation Deciles (IMDD). Results Our study showed the community teledermatology model significantly reduced the active patient’s time and cost to obtain a diagnosis. Average time was 38.1 min, compared to 96.7 min in traditional clinics, saving 58.4 min (95% CI -62.3 to -54.5, p < 0.001). Patients saved £17.9 per diagnosis with this model (95% CI -£19.2 to -£16.6, p < 0.001). Time savings were more substantial for patients from more deprived regions (IMDD 1–3). Conclusion The community-based teledermatology model proves to be cheaper for patients, providing a convenient alternative to traditional clinics, particularly benefiting patients from deprived backgrounds by improving healthcare accessibility and offering flexible consultation options.